Giant otter alarm calls as potential mechanisms for individual discrimination and sexual selection. Issue 3 (1st September 2016) - Leuchtenberger, Caroline; Sousa-Lima, Renata; Ribas, Carolina; Magnusson, William E.; Mourão, Guilherme
Abstract: Acoustic variation can convey identity information, facilitate social interactions among individuals and may be useful in identifying sex and group affiliation of senders. Giant otters live in highly cohesive groups with exclusive territories along water bodies defended by the entire group by means of acoustic and chemical signals. Snorts are harsh alarm calls, emitted in threat contexts, which commonly elicit the cohesion and the alert behaviour of the members of the group. The aim of this study was to determine whether giant otter snorts have potential to be used for individual discrimination. We tested this hypothesis by verifying if the acoustic characteristics of snorts vary between two study areas, among social groups and individuals, and between males and females. Snort acoustic variables did not differ significantly among study areas, but varied significantly among groups, individuals and between sexes, with higher discrimination between sexes. The frequency of formants ( F 1– F 5) and formant dispersion (DF) potentially allow identity coding among groups, individuals and sexes. The stronger sex discrimination of snorts may be related to information on body size carried by formant frequencies and dispersion, indicating acoustic sexual dimorphism in giant otters. Acoustic differences among groups and individuals are more likely learned, since we did not find evidence for a genetic signal encoded in the snort variables measured. We conclude that the snorts carry information that could be used for individual or group recognition.